Comparing space-based to reported carbon monoxide emission estimates for Europe's iron and steel plants - G. Leguijt; G. Leguijt; J. D. Maasakkers; H. A. C. Denier van der Gon; A. J. Segers; T. Borsdorff; I. R. van der Velde; I. R. van der Velde; I. Aben; I. Aben (Atmospheric Chemistry and Physics)
We use satellite observations of carbon monoxide (CO) to estimate CO emissions from European integrated iron and steel plants, the continent's highest-emitting CO point sources. We perform analytical inversions to estimate emissions from 21 individual plants using observations from the TROPOspheric Monitoring Instrument (TROPOMI) for 2019. As prior emissions, we use values reported by the facilities to the European Pollutant Release and Transfer Register (E-PRTR). These reported emissions vary in estimation methodology, including both measurements and calculations. With the Weather Research and Forecasting (WRF) model, we perform an ensemble of simulations with different transport settings to best replicate the observed emission plumes for each day and site. Comparing the inversion-based emission estimates to the E-PRTR reports, nine of the plants agree within uncertainties. For the remaining plants, we generally find lower emission rates than reported. Our posterior emission estimates are well constrained by the satellite observations (90 % of the plants have averaging kernel sensitivities above 0.7) except for a few low-emitting or coastal sites. We find agreement between our inversion results and emissions we estimate using the cross-sectional flux (CSF) method for the seven most strongly emitting plants, building further confidence in the inversion estimates. Finally, for four plants with large year-to-year variability in reported emission rates or large differences between the reported emission rate and our posterior estimate, we extend our analysis to 2020. We find no evidence in either the observed carbon monoxide concentrations or our inversion results for strong changes in emission rates. This demonstrates how satellites can be used to identify potential uncertainties in reported emissions.